Globin chain synthesis in sickle beta-thalassaemic bone marrow and reticulocytes. - Ladas, S (1979)
Globin chain synthesis was studied in reticulocytes and bone marrow erythroid precursors in four sickle beta-thalassaemic Greek patients. Significant globin chain imbalance was found in reticulocytes (alpha/gamma + beta A + beta S = 2.20 +/- SD 0.16) and bone marrow (alpha/gamma + beta A + beta S = 1.58 +/- SD 0.11) after two hours' incubation. There was evidence of contamination of the gamma, beta A, and, to a lesser extent, of the beta S chain by non-haem proteins. The contamination was more obvious in chromatograms obtained from whole cell bone marrow samples and could partially explain the lower alpha/non-alpha ratio found in bone marrow.